Hello! This is my first post over here... I'm taking a college class and doing a proof... I'm stuck on a step -- what do I do next? (~p \/ q) /\ (~q \/ p) = (~p /\ ~q) \/ (q /\ p) great thanks for help!
Follow Math Help Forum on Facebook and Google+
Originally Posted by kcp133 Hello! This is my first post over here... I'm taking a college class and doing a proof... I'm stuck on a step -- what do I do next? (~p \/ q) /\ (~q \/ p) = (~p /\ ~q) \/ (q /\ p) great thanks for help! (~p \/ q) /\ (~q \/ p) <=> [(~p \/ q) /\ ~q] \/ [(~p \/ q) /\ p] <=> [(~p /\ ~q) \/ (q /\ ~q)] \/ [(~p /\ p) \/ (q /\ p)] <=> (~p /\ ~q) \/ (q /\ p)
View Tag Cloud